2004
DOI: 10.1128/jcm.42.7.3073-3076.2004
|View full text |Cite
|
Sign up to set email alerts
|

Use of In Vivo-Generated Biofilms from Hemodialysis Catheters To Test the Efficacy of a Novel Antimicrobial Catheter Lock for Biofilm Eradication In Vitro

Abstract: This biofilm study was conducted to assess the in vitro activity of tetrasodium EDTA on catheters that had been routinely removed from hemodialysis patients at Leeds Teaching Hospitals Trust due to maturation of fistula. Catheters were screened by culture of through-catheter flush, and isolates were identified by standard methodologies; 20 isolates were found to be biofilm positive. Initial biofilm cell count levels averaged above 10 5 CFU/1-cm catheter section. Bacteria identified in the biofilms were gram-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 14 publications
(13 reference statements)
2
72
1
1
Order By: Relevance
“…Continuous exposure to a chelating agent results in cell death through cell lysis. Disodium EDTA used at a dose of 40 mg/ml is capable of completely eradicating K. pneumoniae and P. aeruginosa biofilms on urinary catheters in vitro (64). In the current study, a lower dose of washing of the endometrial surface of the uterine body, indicating that the bioluminescent biofilm-like material produced by lux-labeled P. aeruginosa was strongly adherent and difficult to remove from the endometrium.…”
Section: Figmentioning
confidence: 89%
“…Continuous exposure to a chelating agent results in cell death through cell lysis. Disodium EDTA used at a dose of 40 mg/ml is capable of completely eradicating K. pneumoniae and P. aeruginosa biofilms on urinary catheters in vitro (64). In the current study, a lower dose of washing of the endometrial surface of the uterine body, indicating that the bioluminescent biofilm-like material produced by lux-labeled P. aeruginosa was strongly adherent and difficult to remove from the endometrium.…”
Section: Figmentioning
confidence: 89%
“…Several recent publications have indicated that EDTA alone and in combination is an effective antibiofilm agent with a spectrum covering both Gram-positive and Gramnegative bacteria as well as C. albicans (Raad et al 2003(Raad et al , 2007Kite et al 2004;Percival et al 2005;Banin et al 2006;Sherertz et al 2006). Its antibiofilm effect was suggested to be because of its capability to sequester the divalent ions essential to the extracellular polymeric matrix structure of biofilms (Percival et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cathasept is composed of 4% tetra-sodium ethylene diamine tetra-acetic acid (EDTA) and has both anticoagulant 38,39 and antimicrobial effects 40 and is therefore a potentially useful line lock solution.…”
Section: Introductionmentioning
confidence: 99%